2015
DOI: 10.3390/molecules200814746
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of Photoswitchable Magnetic Au–Fullerosome Hybrid Nanomaterials for Permittivity Enhancement Applications

Abstract: Abstract:We designed and synthesized several nanomaterials 3 of three-layered core-shell (γ-FeOx@AuNP)@[C60(>DPAF-C9)1or2]n nanoparticles (NPs). These NPs having e − -polarizable fullerosome structures located at the outer layer were fabricated from highly magnetic core-shell γ-FeOx@AuNPs. Fullerosomic polarization of 3 was found to be capable of causing a large amplification of material permittivity that is also associated with the photoswitching effect in the frequency range of 0.5-4.0 GHz. Multilayered synt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
19
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6

Relationship

5
1

Authors

Journals

citations
Cited by 6 publications
(20 citation statements)
references
References 20 publications
1
19
0
Order By: Relevance
“…25 In benzonitrile (PhCN), electron-transfer process was found to dominate photophysical events giving the charge-separated (CS) state 1) in a long life-time. 31 A closely linked molecular nanostructure with periconjugation between C 60 > and the carbonyl moiety of DPAF-C n in a spacing distance of only ~3.5 Å 25 and the concurrence of keto-enol tautomerism at the conjugation bridge 29 were reasoned for the observed ultrafast photoresponsive rate.…”
Section: Resultsmentioning
confidence: 98%
See 2 more Smart Citations
“…25 In benzonitrile (PhCN), electron-transfer process was found to dominate photophysical events giving the charge-separated (CS) state 1) in a long life-time. 31 A closely linked molecular nanostructure with periconjugation between C 60 > and the carbonyl moiety of DPAF-C n in a spacing distance of only ~3.5 Å 25 and the concurrence of keto-enol tautomerism at the conjugation bridge 29 were reasoned for the observed ultrafast photoresponsive rate.…”
Section: Resultsmentioning
confidence: 98%
“…Synthesis of 1 followed those steps reported. 29 Sufficient binding of 1-octanethiol as a capping agent on the surface of γ-FeO x @AuNP nanoparticles rendered their moderate solubility in toluene for encapsulation by C 60 (>DPAF- solution. The binding force of C 60 (>DPAF-C 9 ) to the nanoparticle surface was controlled by strong hydrophobic-hydrophobic interaction forces of (C 60 >)-(C 60 >) cages that resulted in a molecular selfassembly of C 60 (>DPAF-C 9 ) molecules to form a partial bilayer or bilayer configuration at the surface, resembling that found on the formation of bilayered fullerosome nanovesicles of water-soluble C 60 (>DPAF-EG x ) reported recently.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…It corresponds to an average of one 1 -C 9 molecule per 1.5 Au atoms (an atomic radius of 0.146 nm) in the product of GN@(FeAuF n ). These atomic ratios led us to roughly estimate a trilayered fullerosome shell thickness on the Au layer of core–shell NPs, consisting of the shell width of ∼8.0 nm reported recently. , Based on the combination of TEM micrographic images and EDS results and analyses, we concluded that the best material component ratios of multilayered GN@(FeAuF n ) nanosheets to be applied in the investigation of their photophysical properties should be either 1.5:1.0:1.5 or 2.0:1.0:2.0 by weight for 1 -C 9 /GN/γ-FeO x @AuNP.…”
Section: Results and Discussionmentioning
confidence: 99%
“…We selected the latter cup -form to undergo further attachment of a C 60 > cage as the end group of each DPAF-C 9 arm that resulted in a nanostructure of tris[60]fullerenylated cis -tris(diphenylaminofluorene) as cis - cup -tris[C 60 (>DPAF-C 9 )] or cis - cup - 3 -C 9 for the photoswitchable dielectric property amplification study. This design of new stereo-isomeric structures may be beneficial for uses as positive charge carriers in enhancing photoinduced dielectric characteristics [ 23 ] and as the precursor building blocks in the synthesis of several C 60 - and C 70 -based ultrafast photoresponsive nanomaterials in correlation to our recent studies [ 17 , 18 , 19 , 20 ]. Therefore, we applied cis - cup - 3 -C 9 as a photoswitchable dielectric charge-polarizer in the fabrication of microwave-responsive plasmonic trilayered core-shell nanoparticles.…”
Section: Introductionmentioning
confidence: 99%